2018
DOI: 10.1212/wnl.0000000000004814
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of restless legs syndrome and total and cardiovascular mortality among women

Abstract: Women with RLS had a higher CVD mortality rate, which may not be fully explained by common co-occurring disorders of RLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 34 publications
(61 reference statements)
0
24
1
1
Order By: Relevance
“…There is considerable comorbidity of RLS with diseases that are particularly common in women [40][41][42][43][44], notably migraine, sleep disorder, depression, and anxiety [3][4][5]44]. The drugs that treat these disorders may, in fact, be the culprits [45][46][47][48][49], as is shown by the fact that RLS symptoms start within days of initiating treatment.…”
Section: Comorbiditymentioning
confidence: 99%
“…There is considerable comorbidity of RLS with diseases that are particularly common in women [40][41][42][43][44], notably migraine, sleep disorder, depression, and anxiety [3][4][5]44]. The drugs that treat these disorders may, in fact, be the culprits [45][46][47][48][49], as is shown by the fact that RLS symptoms start within days of initiating treatment.…”
Section: Comorbiditymentioning
confidence: 99%
“…Several studies showed that RLS might be a prognostic factor for stroke, although others obtained conflicting results ( Table 3 ) [ 230 - 234 ]. In a large prospective cohort study, RLS tended to be associated with an elevated risk of total and cardiovascular mortality, and this association between RLS and mortality increased in women with a longer duration of RLS diagnosis [ 235 , 236 ]. However, two meta-analyses assessing RLS as a risk factor for incident cardiovascular events and all-cause mortality were inconclusive [ 163 , 164 ].…”
Section: Sleep Duration and Insomniamentioning
confidence: 99%
“…The diagnosis of RLS was established using the International Restless Legs Syndrome Study Group (IRLSSG) diagnostic criteria 30 in five studies (35.7%). 31 35 In nine studies (64.3%), the diagnosis of RLS was based on self-administered questionnaires, 4 , 36 38 ICD-9 codes, 5 , 39 and other sleep quesionnaires. 40 , 41 The results of 11 studies (78.6%) 4 , 5 , 31 34 , 36 , 37 , 40 , 41 supported RLS as a risk factor for increased mortality.…”
Section: Resultsmentioning
confidence: 99%